Enhancing the Ecosystem of Central Areas in European Metropolises: A Project for Rome - Eliana Cangelli; Michele Conteduca; Valerio Fonti (Techne)
The paper presents the results of a third-party research project defining the process of redevelopment and social and environmental regeneration along the historic urban axis of Via Nazionale and Corso Vittorio Emanuele II in Rome. The site is affected by the construction of the new tram line connecting Termini Station to the Vatican City. The study proposes an approach to the design of public spaces that, starting by inhibiting traffic from rubber-tired vehicles and private cars and the application of environmental mitigation strategies, allows to reduce pollutant emissions, enhance the cultural heritage along the urban axis, and revitalise cultural, social, and commercial activities, thus triggering a virtuous process of sustainable growth and development.